Social Work, Mobility and Membership - Bill Jordan (Social Work and Society, 2003)
Social work is more involved in the collective life of its clientele than are other human service activities, because it is directly concerned with the bonds and conflicts between individuals, and the co-operative and competitive aspects of groups and communities. Hence it relies on being sited in organisations relevant to service users’ lives, and on being able to influence these collectivities. This article argues that the ‘organisational landscape’ is being transformed, as commercial enterprises (more mobile and adaptable than either state or non-government organisations) take over important aspects of collective provision. The implications of this transformation for practice are analysed, by reference to examples from the United Kingdom in particular.